Taxonomic revision of Mycolybas Crotch, 1876 (Coleoptera: Erotylidae) - Lopes, Peterson L. (Zootaxa, 2006)
A taxonomic revision of Mycolybas Crotch, 1876 is proposed. Historically the genus comprised seven species: M. coccineipennis (Motschulsky, 1858), M. cruentatus (Kirsch, 1865), M. egae Crotch, 1876, M. lucidus (Lacordaire, 1842), M. melanocorynus (Lacordaire, 1842), M. rufipennis Guérin, 1956 and M. sanguinosus (Motschulsky, 1858), recorded from Central and South America. After a morphological analysis, new diagnostic characters were discovered (i.e. armed laciniae for M. coccineipennis, and tarsal sexual dimorphism for M. lucidus and two new species). Three species are regarded as synonymies of M. lucidus (M. cruentatus syn. nov., M. egae syn. nov., M. melanocorynus syn. nov.), four are redescribed (M. coccineipennis, M. lucidus, M. rufipennis and